Stabilization of Unmanned Air Vehicles over Wireless Communication Channels - Qing-Quan Liu (Universitas Ahmad Dahlan, 2013)
This paper addresses the stabilization problem for unmanned air vehicles over digital and wireless communication channels with time delay. In particular, the case with band-limited channels is considered. An observer-based state feedback control policy is employed to stabilize the linear control system of unmanned air vehicles. A sufficient condition on the minimum data rate for mean square stabilization is derived, and a new quantization, coding, and control policy is presented. Simulation results show the validity of the proposed scheme.